2005
DOI: 10.1590/s0103-21002005000400004
|View full text |Cite
|
Sign up to set email alerts
|

Atitudes de alunos e enfermeiros frente ao diagnóstico de enfermagem: attitudes of nurses and nursing students

Abstract: INTRODUÇÃO: No processo de enfermagem proposto por Horta, o termo diagnóstico de enfermagem (DE) foi substituído por problemas de enfermagem, reaparecendo na literatura brasileira no final da década de 80. Desde então, as enfermeiras vêm se apropriando do conhecimento sobre os conceitos diagnósticos, especialmente a classificação de DE da North American Nursing Diagnosis Association. OBJETIVOS: Descrever as atitudes de enfermeiros e estudantes de enfermagem em relação ao conceito DE e analisar as associações e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
21

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 2 publications
(3 reference statements)
2
10
0
21
Order By: Relevance
“…The PND-7-SV demonstrated excellent detec on of relevant changes in a tudes mediated by an interven on implemented with that objec ve. The change in the a tude detected by the scale in the students who a ended the educa onal ac vity, supports the results of previous studies (8,18) that found an associa on between having received educa on in nursing diagnosis and having a more favorable a tude towards it.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The PND-7-SV demonstrated excellent detec on of relevant changes in a tudes mediated by an interven on implemented with that objec ve. The change in the a tude detected by the scale in the students who a ended the educa onal ac vity, supports the results of previous studies (8,18) that found an associa on between having received educa on in nursing diagnosis and having a more favorable a tude towards it.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies (8,18) associate the use of nursing diagnosis and educa on in the subject with posi ve a tudes towards the concept. The ability of the scale to detect changes in the scores in the same subject, between the situaon before and a er comple ng the educa onal ac vity, was evaluated through the paired t-test, by checking the hypothesis of changes in a tudes.…”
Section: Sta S Cal Analysismentioning
confidence: 99%
“…Several investigators found that nurses might not be willing to use ND because of lack of time, lack of education related to ND (Paganin, Moraes, Pokorski, & Rabelo, 2008;Whitley & Gulanick, 1996), and negative attitudes toward ND (da Cruz Dde, Hayashi, Oliva, & Correa, 2006;Lunney & Krenz, 1992;Paans et al, 2011). However, when nurses' attitudes toward ND are positive, they use ND more effectively (Oliva, de Almeida Lopes, Volpato, & Hayashi, 2005). It was also shown that the positive attitude toward ND improves over time after its introduction in Pimenta, & da Costa Lima, 2006) and that the more nurses use and interact with ND the more positive their attitudes toward it ).…”
Section: Introductionmentioning
confidence: 99%
“…The scale can be used in all clinical settings by nursing students and clinical nurses and is currently used in the US, Brazil, Japan, Spain, and India (Collins, 2013;Hasegawa, Ogasawara, & Katz, 2007;Lunney & Krenz, 1992;Oliva et al, 2005;. The PND is simple to use, fast to administer, highly versatile, and sensitive to small differences in attitude.…”
Section: Introductionmentioning
confidence: 99%
“…Não foi mencionado por nenhum dos enfermeiros especialistas, apenas pela investigadora, isto pode ter ocorrido pelo fato da investigadora ser estudante do curso de graduação, o que lhe confere um maior contato com os novos DE o que não ocorre com os enfermeiros. Este fato indica a necessidade de atualização por meio de pesquisa ou educação continuada (15) . Em São Paulo, a prevalência de DPOC varia de 6% a 15,8% em pacientes com idade igual ou superior a 40 anos (16) .…”
Section: Discussionunclassified